Homemade 3-carbon electrode system for electrochemical sensing: Application to microRNA detection - Carneiro, Mariana C.C.G. (2018)
The homemade production of carbon screen-printed electrodes (C-SPEs) with a three‑carbon electrode system is reported, along with its application in electrochemical sensing. It is highlighted herein as main novelty that a simple carbon ink may be employed in the preparation of the 3-electrode system, including the pseudo-reference electrode, thereby avoiding the addition of silver or other suitable metal and simplify the construction of such devices, reducing costs and time. Screen-printed technology was employed to produce the 3-electrodes and the corresponding electrical paths. This was achieved by the manual application of a commercial carbon ink into a polyvinyl chloride (PVC) substrate allowing the production of > 20 SPEs. The optimization of the SPE assembly was made by univariate mode, until the best electrical features of the electrode-solution interface were achieved. Several electrochemical techniques were used for this purpose, namely cyclic voltammetry (CV), square wave voltammetry (SWV) and electrochemical impedance spectroscopy (EIS). Raman Spectroscopy and Thermogravimetric Analysis (TGA) were also used for materials and electrode surface characterization. The usefulness of such devices was tested by modifying the working electrode with a sensing layer for microRNA-107, a potential biomarker in Alzheimer's Disease (AD). For this purpose, the surface was functionalized with carboxylic groups, activated by carbodiimide reaction and bound to a suitable oligonucleotide probe containing the complementary sequence. Finally, the microRNA-107 sequence hybridized with its probe, proving the efficiency of the C-SPEs in electrochemical sensing. Overall, this study brings into light the possibility of preparing simple homemade electrodes with a 3‑carbon electrode system that stands out by the low cost, disposability and versatility of the presented platform, holding a great potential for application in point-of-care devices using electrochemical sensing.